2006
DOI: 10.1093/bioinformatics/btl107
|View full text |Cite
|
Sign up to set email alerts
|

DRTF: a database of rice transcription factors

Abstract: DRTF is available at http://drtf.cbi.pku.edu.cn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(108 citation statements)
references
References 13 publications
0
107
1
Order By: Relevance
“…The actual number of genes in our data set is between 2,513 (the minimum number of genes) and 2,882 (the total number of sequences). This value is greater than the predicted number of TFs present in Arabidopsis (1,922) and rice (O. sativa indica, 2,025, O. sativa japonica, 2,384; Guo et al, 2005Guo et al, , 2006 and equivalent to that reported in poplar (2,576; Zhu et al, 2007). N. tabacum is considered to be an ancient allotetraploid (2n 5 4x 5 48) resulting from an interspecific hybridization event between Nicotiana sylvestris and Nicotiana tomentosiformis (Goodspeed, 1954;Murad et al, 2002).…”
Section: Tfs In the Tobacco Genomementioning
confidence: 65%
See 3 more Smart Citations
“…The actual number of genes in our data set is between 2,513 (the minimum number of genes) and 2,882 (the total number of sequences). This value is greater than the predicted number of TFs present in Arabidopsis (1,922) and rice (O. sativa indica, 2,025, O. sativa japonica, 2,384; Guo et al, 2005Guo et al, , 2006 and equivalent to that reported in poplar (2,576; Zhu et al, 2007). N. tabacum is considered to be an ancient allotetraploid (2n 5 4x 5 48) resulting from an interspecific hybridization event between Nicotiana sylvestris and Nicotiana tomentosiformis (Goodspeed, 1954;Murad et al, 2002).…”
Section: Tfs In the Tobacco Genomementioning
confidence: 65%
“…Seven of the nine largest TF gene families in tobacco are very similar in size and complexity to their counterparts in Arabidopsis, rice, and poplar (Guo et al, 2005;Gao et al, 2006;Zhu et al, 2007). This allowed us to identify possible functional homologs in tobacco of genes characterized in other plant species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 2384 known or annotated TF genes in the rice gnome [27], 196 (8.2%) were observed to be differentially regulated by cold in this study (Additional file 14). These TF genes include 26 AP2/EREBP, 21 bHLH, 7 HSF, 19 MYB, 12 NAC, and 17 WRKY genes.…”
Section: Resultsmentioning
confidence: 97%